2018
DOI: 10.1016/s2542-5196(17)30181-x
|View full text |Cite|
|
Sign up to set email alerts
|

Ambient carbon monoxide and cardiovascular mortality: a nationwide time-series analysis in 272 cities in China

Abstract: Public Welfare Research Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 27 publications
12
105
2
Order By: Relevance
“…Globally, air pollutant levels are disproportionately higher in urban centers compared to rural settings [100, 41, 40, 101103, 86, 32, 104]. Acute exposure to both PM 2.5 and PM 10 led to acute rises in arterial blood pressure (BP) in urban centers in the US mostly inhabited by minority groups, namely African Americans [57, 52].…”
Section: Urban Vs Ruralmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, air pollutant levels are disproportionately higher in urban centers compared to rural settings [100, 41, 40, 101103, 86, 32, 104]. Acute exposure to both PM 2.5 and PM 10 led to acute rises in arterial blood pressure (BP) in urban centers in the US mostly inhabited by minority groups, namely African Americans [57, 52].…”
Section: Urban Vs Ruralmentioning
confidence: 99%
“…These Asian megacities have air pollution levels up 10 times the US NAAQS [38, 37]. In a nationwide time-series analysis in 272 major Chinese cities, both short-term exposure to SO 2 (per 10μg/m 3 increments) and CO (per 1 μg/m 3 increments) were associated with a 0.70% increase and a 1.12% increase in overall CVD mortality, respectively [41, 42]. In a meta-analysis of 59 studies from China where mean PM 2.5 exposures were between 39 to 177 μg/m 3 , each 10μg/m 3 increment was associated with a 0.63% increase in overall CVD mortality [37].…”
Section: Developed Vs Developing Countriesmentioning
confidence: 99%
“…A positive correlation between CO and total dynamic stroke mortality and dynamic mortality in both age categories was observed, which is also consistent with previous studies. Liu et al demonstrated that short‐term exposure to ambient CO was associated with increased mortality from cardiovascular disease in China . The reason why a correlation between CO and total stroke mortality was apparent only during the cold season may be explained by the higher concentrations of CO that occur at this time of the year because of increased fuel use.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies investigating the effect of air pollution on the risk of stroke have used different indicators of stroke risk . Hospital admissions have been extensively used to correlate long‐term exposure to air pollution and other risk factors with stroke .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation